MANFAAT DAUN BINAHONG DALAM MASKER ORGANIK TERHADAP PENGURANGAN JERAWAT PADA REMAJA USIA 12 – 18 TAHUN - Pinkan Duan Tirani; Novita Sabila Ramdhani, Rheyda Vhegals Christiani (ADISAM PUBLISHER, 2024)
Facial skin problems during adolescence can be a very scary thing for both male and female teenagers. Facial skin problems that often appear in adolescence are acne and dull skin, acne appears at puberty, namely at the age of 10-18 years. Facial skin care to reduce acne can be done using 2 methods, namely modern or traditional methods. Using organic masks is one way to care for facial skin using traditional methods. By utilizing surrounding natural resources such as surrounding plants, one of which is binahong leaves. The main aim of the research was the researchers' desire to know about the effectiveness of natural masks made from binahong leaves in treating acne problems in adolescents aged 12 - 18 years, with a sample of 10 people who had acne on their faces. The sample used masks 1 week 3 times for 1 month. From the results of data analysis, it shows tcount = 4.00, α = 0.05, dk)= 8, and t table= 1.89, the result is tcount>ttable, the null hypothesis (Ho) is rejected, this proves that the use of binahong masks Very effective for teenage acne sufferers